Treatment of Tinnitus in Children—A Systematic Review - Dullaart, Max J.; Kip, Marijn; Smit, Adriana L.; Stegeman, Inge (Frontiers in Neurology, 2021)
Objectives: To systematically review studies on the effect of treatment of subjective tinnitus in children. Data sources: We searched for studies in in MEDLINE and EMBASE databases, after which additional studies were handsearched using Scopus databases. The methods are described in the study protocol, which has been registered in the PROSPERO register. PRISMA guidelines were followed in the reporting of this study. Eligibility criteria: We considered randomized controlled trials (RCTs), observational studies, case reports and case series, which provided outcomes for children (0 – 18 years old) with acute or chronic subjective tinnitus, for inclusion. We excluded animal studies and studies with a non-original study design, as well as studies about children with pulsatile or objective tinnitus or tinnitus exclusively due to (sudden) sensorineural hearing loss. Data selection: Two reviewers independently assessed studies for eligibility and quality, collected and extracted data. Statistical analyses were performed in case of homogeneous outcomes. Results: The search yielded a total of 4,447 studies, of which 147 eligible studies were selected and one case report and 5 observational studies met the eligibility criteria. Three studies applied counseling and (simplified-)TRT and reported improvement in tinnitus outcome in 68 out of 82 children after three to six months of treatment. Two used pharmacological treatments and reported improvement in 74 out of 86 patients after 10 days to 3 months of treatment. One reported the outcome of biofeedback therapy, describing an improvement in tinnitus loudness and annoyance after two months of treatment. Conclusion: Due to the high risk of bias of the included studies, we cannot determine the effectiveness of the treatment of subjective tinnitus in children. Also, owing to brief follow-up periods, it is not possible to draw conclusions regarding long-term effects. Randomized controlled trials with longer follow-up periods are necessary to provide substantial evidence of the effects of therapies for children affected by tinnitus. Protocol registration number: CRD42020178134